One true theory & the quest for an American aesthetic - Banta, Martha (Yale University Press, 2007)
"Counter Martha Banta reaches across several disciplines to investigate America's early quest to shape an aesthetic equal to the nation's belief in its cultural worth. Marked by an unusually wide-ranging sweep, the book focuses on three major 'testing grounds' where nineteenth-century Americans responded to Ralph Waldo Emerson's call to embrace 'everything' in order to uncover the theoretical principles underlying 'the idea of creation.' The interactions of those who rose to this urgent challenge artists, architects, writers, politicians, and the technocrats of scientific inquiry brought about an engrossing tangle of achievements and failures. The first section of the book traces efforts to advance the status of the arts in the face of the aspersion that America lacked an Art Soul as deep as Europe's. Following that is a hard look at heated political debates over how to embellish the architecture of Washington, D.C., with the icons of cherished republican ideals. The concluding section probes novels in which artists' lives are portrayed and aesthetic principles tested."--Provided by publisher.
Keywords: Aesthetics, American.; Arts -- United States.; Esthétique américaine.; Aesthetics, American; Arts; United States; Ästhetik; USA